Madrasa teacher professionalism: Effects of gender and teaching experience in learning - Syahraini Tambak; Amril Amril; Desi Sukenti; Muhammad Yusuf Ahmad; Hamzah Hamzah; St. Marwiyah (International Journal of Evaluation and Research in Education (IJERE), 2022)
Developing professional madrasa teachers are increasingly popular in the classroom, but of these teachers, mixed results (without clear reasons) are reported. This article addresses the impact of gender and teaching experience (duration) on developing professional madrasa teachers, using the two factors as references. Research with a questionnaire was conducted in 75 public and private Aliyah Madrasas, with data collected from 325 teachers. Data analysis is differentiated based on madrasa teachers’ type (public or private), gender, and teaching experience in the competencies assessed. Results showed that developing professional teachers’ proficiency is low and related to gender, that males perceive themselves more highly developed professionally than females, and that even teaching experience does not necessarily ensure development of professional competence and implementation in the classroom. The development of professional madrasa teachers with more than 30 years’ experience is less proficient than that of teachers with experience from 21–30, 10–20, and <10 years. However, the significant relationship between gender and professional development of madrasa teachers who have taught for more than 30 years is revealed: the development of male madrasa teachers who have taught for more than 30 years is less proficient than that of females. Reasons behind this difference must be examined and competencies differentiated to improve development of professional madrasa teachers’ professionalism.